Multiple congenital epuli (congenital granular cell tumours) in the newborn: a case report and review of literature - Dzieniecka, Monika; Komorowska, Anna; Grzelak-Krzymianowska, Adriana; Kulig, Andrzej (Polish Journal of Pathology, 2011)
Congenital epulis of newborn is very rare benign intraoral entity of uncertain ethiology. Histologically the lesion is similar to the granular cell tumour of an adult but immunohistochemical stainings prove their different origin. Treatment involves surgical excision, recurrences are rare.